2005
DOI: 10.1080/13547500500264645
|View full text |Cite
|
Sign up to set email alerts
|

Application of two SH-based methods for metallothionein determination in mussels and intercalibration of the spectrophotometric method: laboratory and field studies in the Mediterranean Sea

Abstract: Metallothionein (MT) induction is widely used as a biomarker of exposure to metals in mussels. The aims of the present work were first to compare the suitability of spectrophotometry and differential pulse polarography (DPP) for MT detection in mussels exposed to 200 ppb cadmium for 9 days in a laboratory experiment and in mussels sampled in different seasons from expected pollution gradients along the Mediterranean Sea; second, to intercalibrate the widely used spectrophotometric method using mussels from Sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 50 publications
1
9
0
4
Order By: Relevance
“…Considering heavy metal detoxification significance of MTs, these proteins can serve as biomarker of heavy metal pollution of the environment [12][13][14][15]. On the other hand, a comparison between the content of heavy metals and determined MTs could be very useful not only from ecotoxicological aspects but also from biochemical aspects due to the better understanding of different functions of MTs in an organism [16].…”
mentioning
confidence: 99%
“…Considering heavy metal detoxification significance of MTs, these proteins can serve as biomarker of heavy metal pollution of the environment [12][13][14][15]. On the other hand, a comparison between the content of heavy metals and determined MTs could be very useful not only from ecotoxicological aspects but also from biochemical aspects due to the better understanding of different functions of MTs in an organism [16].…”
mentioning
confidence: 99%
“…Moreover, acetylcholinesterase (AChE) has been widely used as enzymatic biomarker of neurotoxicity for aquatic organisms after exposure to pollutants (Rickwood and Galloway, 2004). Numerous previous studies have also demonstrated metallothionein (MT) as an indicator of heavy-metal exposure (Viarengo et al, 1997;Zorita et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In field studies, MT values obtained by DPP were 34-to 38-fold higher than with spectrophotometry, and the MT concentrations measured by both methods were not correlated. This discrepancy could be due to several factors, including the low levels of bioavailable metals in the studied areas and the possibility that the different methods can measure MT isoforms differentially [12]. Also, another study showed a good correlation between results obtained, for instance, using DPP and a metal saturation assay [70] and between DPP and spectrophotometric determination [73].…”
Section: Discussionmentioning
confidence: 91%